SIMPLE METHODS FOR ESTIMATION OF PARAMETERS FOR ASSESSING EXPLOITED FISH STOCKS - Alagaraja, K (Indian Journal of Fisheries, 2011)
New methtxls for estimation of growth and mortality parameters, togetherwith their error estimations, are given, discussing in detail their advantages overthe existing ones. A new model called Relative Response model has been designedfor estimation of such stocks that are common in tropics where the applicationof other models are not effective. Demonstrative worksheets are provided to illustrateeasy working of the methods. Various proformae for collection of data areappended.